Effect of wood flour as carbon source on cellulases and xylanases production by white-rot-fungi native from Misiones - Rodríguez, M. D.; Barchuk, M. Lucrecia; Fonseca, M. Isabel; Zapata, Pedro D; Villalba, Laura Lidia (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
There is a need to explore lignocellulosic materials to select an adequate substrate for lignocellulolytic enzyme production. Utilization of some residues provides an opportunity to produce high yields of lignocellulolytic enzymes in a simple medium. The aim of the present work was to study the effect of wood flour as a carbon source on the cellulolytic and xylanolytic secretion of white-rot fungi native from Misiones. Fungi were incubated with 5 g Pinus sp. wood flour/L and 5 g Eucalyptus sp. wood flour/L as carbon sources in a reciprocal shaker at 80 rpm and 29ºC for 15 days. Total cellulase, endo-1,4-Î²-glucanase, Î²-glucosidase, cellobiohydrolase and endo-1,4-Î²-xylanase activities were determined in culture supernatants. Tested fungi showed high endo-1,4-Î²-xylanase activity between 6 and 12 days. Total cellulase showed the highest activity between 12-15 culture days. The test did not show differences among Pycnoporus sanguineus LBM 014, P. sanguineus BAFC 2126, Irpex lacteus BAFC 1171, Irpex sp. LBM 032, Irpex sp. LBM 034 and Lenzites elegans BAFC 2127, showing the highest activity for this group regard the others strains. I. lacteus BAFC 1171 was the strain with major endo-1,4-Î²-glucanase activity at day 9 (847 U/L). In the case of Î²-glucosidase and cellobiohydrolase, P. sanguineus BAFC 2126 was the strain with the highest activity between 12-15 culture days (18 U/L), and between 9-15 culture days (39 U/L), respectively. Wood flour proved to be a suitable carbon source to produce hydrolytic enzymes. I. lacteus BAFC 1171 and P. sanguineus BAFC 2126 have potential for cellulase production whereas P. sanguineus LBM 008 is a good endo-1,4-Î²-xylanase producer.